Alberto's life story: transforming a disadvantaged school by appreciating the child's voice. (2nd October 2021) - Lucena Rodríguez, Carmen; López, Alberto; Domingo Segovia, Jesús; Cruz González, Cristina
ABSTRACT : This article present a case study of a principal who successfully leads a disadvantaged school in Spain. Through his life story, we investigate the personal and professional factors that have shaped his current professional identity, and we identify the main successful educational practices that the principal has implemented in order to achieve improvements in educational outcomes. Findings reveal a set of professional practices that have been invigorated from his leadership for the improvement of education. In short, he is committed to leading by appreciating the voice of the child and having respect for the children and it is this that forms part of the collective ideology of the school and is the most outstanding role of his professional identity.